Full reoxidation of CuMn2O4 spinel catalyst triggered by epitaxial Mn3O4 surface nanocrystals. Issue 11 (27th June 2017) - Trapp, Maximilian; Müller, Mathis M.; Nazarpoor, Zahra; Kleebe, Hans‐Joachim
Abstract: Transmission electron microscopy was performed on a model system of a novel CuMn2 O4 spinel catalyst in order to study the effects of reduction by carbon monoxide and subsequent reoxidation by oxygen both processed at 600°C. A phase transition from CuMn2 O4 spinel into separated MnO and Cu‐rich phases, which are CuO or Cu depending on the reduction period, was observed in the reduced samples. Furthermore, a surface coverage of the MnO grains by epitaxially grown, nanocrystalline Mn3 O4 was found in all reduced samples. These Mn3 O4 nanocrystals are assumed to act as seed crystals in the subsequent reoxidation step completely reversing the phase transitions and reconstituting single‐phase CuMn2 O4 spinel. In addition, superlattice reflections due to cation ordering occurred as a typical feature in the as‐prepared spinel. In the reoxidized spinel, the superlattice reflections were absent, hence indicating a disordered cation distribution.